An Analysis of the Criminalization of Forced Marriage from the Perspective of Dzari'ah Theory - Sunarto, Muhammad Zainuddin; Fadil, Fadil; Suwandi, Suwandi (JURNAL AT-TURAS, 2024)
The practice of forced marriage that is cultured in society has many negative effects, one of which is that women are a group that is vulnerable to various forms of domestic violence, both physically, psychologically, sexually, and economically. Criminal law is expected to overcome the high rate of domestic violence that occurs due to forced marriage. In the case of forced marriage, criminal law is important in anticipation of domestic violence. The focus of this research is how forcing marriage as a criminal act uses the theory of dzari'ah. The factors that affect the occurrence of forced marriage are patriarchal culture and ideology that are socialized in society. In the patrilineal system, marriage is often a tool to strengthen inter-clan or family relationships. The correlation between forced marriage and the right of ijbar wali shows that the practice of forced marriage in the community is also greatly influenced by the right of ijbar wali. The criminalization of forced marriage has been by dzari'ah, in practice there is a certain motivation from the perpetrator of coercion to make the victim forced to carry out marriage on the one hand, and on the other hand, the consequences arising from the marriage on which one of the spouses is forced to carry out the marriage. The TPKS Law has translated the basic values of Grundnorm into daily legal practice. This shows how the implementing norm expresses Grundnorm's values through concrete legal sanctions that are in line with the mandate of the 1945 Constitution to protect citizens.